Efektifitas Penggunaan Metode Talking Stick dalam Pembelajaran Tamrin Kelas I Reguler Marhalah Tsanawiyah TMI Pi Al-Amien Prenduan tahun 2021 - Sherly Quraisy; Asmaniyah Asmaniyah (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2021)
The purpose of this research is to see how effective the talking stick method is for learning Tamrin class I Marhalah Tsanawiyah TMI Putri Al-Amien Prenduan. This research uses quantitative and experimental research methodologies in a single class. The researcher employed a pretest in this procedure. This research's population consisted of regular first-class female students, totaling 221 female students, with a sample of 10% of the population, namely regular class I students "B," totaling 22 female students. The Tamrin material test, observation, and documentation were employed as research instruments in this study. The T-test formula is a statistical data analysis methodology that was utilized. The calculated T-test value was 2.275, based on the results of the tests performed. dk = n-1 = 22-1 = 21 in this case. T-test table = 1.721 is calculated with dk = 21 and a margin of error of 5%. T-table (2.275 > 1.721) has a higher value than T-count (2.275 > 1.721). As a result, Ha was accepted whereas Ho was refused, indicating that adopting the talking stick method in Tamrin learning improved learning outcomes.